Is mean platelet volume the earliest diagnostic marker of neonatal sepsis: a prospective case control study - Pandian, Ramkumar; Kugonally, Gopal; R., Lakshmipathy S.; ., Sunitha (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal sepsis is the third leading cause of neonatal mortality after prematurity and intrapartum related complications worldwide. The literature regarding the use of Mean platelet volume as a diagnostic tool in neonatal sepsis is scanty. Methods: Prospective case control study in a district hospital. Neonates > 30 weeks gestation admitted to NICU during the study period were included. Neonates who did not have any risk factors for sepsis and did not have a positive blood culture or elevated CRP were categorized as group 1. Neonates who were admitted with risk factors of sepsis but did not have a positive CRP or blood culture positivity were categorized as group 2. Neonates who were admitted as probable sepsis and subsequently developed blood culture or CRP positivity were categorized as group 3.Septic workup was done for all the subjects at admission and at 72 hours after admission. Newborn with congenital anomalies and who were already on antibiotics prior to admission were excluded from the study. Statistical analysis was done using Statistical Package of Social Sciences (SPSS) version 20.0. Results: Total 240 Neonates were included in the study. Elevation of MPV in neonates with sepsis was seen as early as the first sample whereas CRP elevation was seen only on Day 3. Cut off value for Mean Platelet Volume (MPV) was found to be 10.15fl with sensitivity of 84% and specificity of 74%. Conclusions: MPV can be used as a earliest diagnostic marker for prediction of neonatal sepsis and mortality. It can facilitate early initiation of treatment without any additional exposure.